2002
DOI: 10.1002/ajim.10123
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic and porphyrins

Abstract: The increase of urinary excretion for some porphyrin homologues appears to be consistent with the inhibition by As of URO-decarboxylase in the heme biosynthesis pathway. The determination of urinary porphyrin homologues could be useful to assess, on a group basis, some early effects of arsenic and to demonstrate possible individual susceptibility to the element.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
1
3
0
1
Order By: Relevance
“…The author obtained a direct relationship between timeweighted exposure to arsenic and alterations in urinary porphyrin excretion ratios with a lower uroporphyrinogen decarboxylase activity in arsenic exposed individuals. Similar observations were also noted by Ng et al [12], Wang et al [35] and Xie et al [43] in their studies of urinary porphyrins among the subjects exposed to arsenic due to coal burning in China and also by Telolahy et al [36] and Apostoli et al [44] in their studies of urinary porphyrins, respectively in smelter workers and art glass workers. The hepta I levels obtained in the present study were found to be lower compared to the two porphyrins, uro III and copro III, in exposed and control population.…”
Section: Mda (µMol/g Creatinine)supporting
confidence: 84%
“…The author obtained a direct relationship between timeweighted exposure to arsenic and alterations in urinary porphyrin excretion ratios with a lower uroporphyrinogen decarboxylase activity in arsenic exposed individuals. Similar observations were also noted by Ng et al [12], Wang et al [35] and Xie et al [43] in their studies of urinary porphyrins among the subjects exposed to arsenic due to coal burning in China and also by Telolahy et al [36] and Apostoli et al [44] in their studies of urinary porphyrins, respectively in smelter workers and art glass workers. The hepta I levels obtained in the present study were found to be lower compared to the two porphyrins, uro III and copro III, in exposed and control population.…”
Section: Mda (µMol/g Creatinine)supporting
confidence: 84%
“…Our findings for uro (5.3 ± 6.0 μg/g creatinine), copro (41.0 ± 25.2 μg/g creatinine) and uro + copro porphyrins (46.2 ± 26.3 μg/g creatinine) agree with the data reported by Buratti et al (34) for total porphyrins. Apostoli et al (10) detected higher values for uro, copro, and uro + copro porphyrins, namely 9.4 ± 11.4, 70.5 ± 36.7, and 89.8 ± 44.8, respectively, using analytical methodology similar to that which we used. The differences found could, therefore, be attributed to the different populations studied.…”
Section: Discussionmentioning
confidence: 67%
“…These conditions have been observed after exposure to chemicals such as polychlorinated biphenyls (5), hexachlorobenzene (6), pentachlorophenol (1,7), and dioxins (8) and heavy metals such as arsenic (9,10), Hg (3), and Pb (11). They can also occur in individuals infected by some viruses such as HBV (12), HCV (12)(13)(14), and HIV (15,16) or exposed to illicit or therapeutic drugs like alcohol (17), to prolonged therapeutic use of estrogens (18) and to iron overload (13), and as adverse effects of drugs like anticonvulsants (19) and anesthetics (20).…”
Section: Introductionmentioning
confidence: 99%
“…Expérimentalement, chez le rat et la souris, il inhibe la synthétase de l'acide delta-aminolévulinique et la ferrochélatase, les enzymes qui catalysent la première et la dernière étape de la synthèse de l'hème, ainsi que la coproporphyrinogène oxydase [117][118][119] ; il augmente l'activité de l'uroporphyrinogène-1-synthétase. Des élévations de l'excrétion urinaire des coproporphyrines et des uroporphyrines ont été observées dans des populations humaines exposées à l'arsenic [120][121][122], mais ces perturbations sont encore mal caractérisées [123]. En outre, il existe de nombreuses autres causes d'altérations de l'élimination urinaire des porphyrines.…”
Section: Indicateurs Biologiques D'effets Précocesunclassified